Cross-Dynastic Intergenerational Altruism - Frikk Nesje (ZBW - Leibniz Information Centre for Economics, 2021)
This paper studies whether saving behavior reveals socially relevant intertemporal preferences. I decompose the present generation's preference for the next into its dynastic and cross-dynastic components. If people are concerned about sustainability or if their descendants move or marry, then they might assign welfare weights on other dynasties. With such cross-dynastic intergenerational altruism, saving for one's descendants benefits present members of other dynasties. These preference externalities imply that socially relevant intertemporal preferences cannot be inferred from saving behavior. The external effect of present saving decreases over time. This means that intertemporal preferences inferred from saving behavior are time-inconsistent.
Keywords: D64; D71; H43; Q01; Q54; 330; Intergenerational altruism; Social discounting; Time-inconsistency; Declining discount rates; Generalized consumption Euler equations; Interdependent utility; Isolation paradox; Climate change